Responses to injured conspecifics and heterospecifics by water fleas, Chydorus sphaericus. Issue 6 (1st November 2016) - Pecor, Keith; Sarris, Thomas; Shaffer, Justin; Thom, Eric
Abstract: Cladocerans have been shown to exhibit a variety of responses to chemical stimuli associated with predation risk, including those from predators and injured conspecifics. In this study, we tested the hypothesis that individuals of Chydorus sphaericus would respond with avoidance behavior to chemical cues from both injured conspecifics and injured heterospecifics. Avoidance behavior was seen in response to cues from C. sphaericus and Daphnia magna . Responses to cues from Daphnia pulex were intermediate between those of the other cues and the water control. We propose that a concentration effect may be responsible for the mixed responses to heterospecific cues and speculate that responses to a broad range of cues may help explain the expansive range of C. sphaericus .